Law relating to women and child - O P Mishra (Allahabad Central Law Agency, 2020)
It is a matter of great pleasure that Sixth edition of the book "Law Rolwing to Women & Child" la bringing out for the respectable readers. The present edition of die book has been up-dated by incorporating latest case laws and amendments on the relevant. It is hoped that it would be belpful and interesting to those concerned for pruunction of women & children in our country and also for the LL.B. and LL.M. Students of various Universities. I am grateful to Ms. Central Law Agency for bringing out the Sixth edition of the book.
Keywords: Cruelty and Dowry Death; Position of Women; Kidnapping and Abduction; Minority and Guardianship; Child Marriage